Life and Intrigues at the Court of the King Henry VIII. - Hladíková, Nikola (Univerzita Pardubice, 2014)
The aim of this bachelor thesis is to analyse a treatment of historical events and processing of literary characters and comparing them with real events and historical personages. The primary source is a historical novel Wolf Hall written by a British writer, Hilary Mantel. This bachelor thesis examines the intrigues and life at the court of Henry VIII and closely analyse the characters that spin those intrigues.
Život a intriky na dvoře krále Jindřicha VIII.
Keywords: Wolf Hall; Cromwell, Thomas; Boleynová, Anna; tudorovští králové; Mantel, Hilary; Jindřich VIII; Wolf Hall; Cromwell, Thomas; Boleyn, Anne; tudor kings; Wolsey, Thomas; Mantel, Hilary; Henry VIII